(untitled) (Panacea Journal of Medical Sciences, 2022)
Background: Multiple scoring systems have been addressed to identify those patients who need emergency appendicectomy as the risk of delay could be avoided. Of these, the consideration of both sore related to the Alvarado and Tzanakis is essential for the study to understand the effective diagnose of acute appendicitis. Aim: The study aims to compare and evaluate Alvarado and Tzanakis score for diagnosing the acute appendicitis. Materials snad Methods: This study was conducted in the department of General Surgery associated with the M.K.C.G, Medical College and Hospital, Berhampur from August, 2018 to July, 2020. A total of 96 patients were being considered for carrying out a systematic study after carefully verifying a variety of the inclusion and exclusion criteria. To conduct the study in a systematic manner, the doctor has analyzed and given the score of Alvarado and Tzanakis. On the basis of score of these two approaches, the medical team has provided the treatment to these patients. The proper identification of score has helped to select the method of operation and surgery. In addition to this, the comparison of score focusing on the NPV and PPV has also allowed for identifying the sensitivity. Results: The Alvarado and Tzanakis score was found to have sensitivity along with the specificity of 94.44% and 83.33% respectively. However, the PPV and NPV was found to be 98.84% and 50.00% respectively as compared to Alvarado score where sensitivity, specificity, PPV and NPV was found out to be 77.77%, 66.66%, 97.22% and 16.66% respectively. Conclusion: From the study, it has carried out that the Tzanakis scoring system has been addressed a more reliable for analyzing the condition of patients and offering the treatment. Diagnostic. Alvarado score, with the former achieving higher sensitivity and PPV.